2014
DOI: 10.9790/7388-04146789
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian Foreign School Teachers’ Perception And Capability To Undertake Classroom Action Research: Basis For Capability Building Program

Abstract: This academic study which is taken from March to October 2012 is anchored on the Theory of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…However, only 39 lecturers responded to the questionnaire and returned it. The instrument used in this study was a questionnaire which was adapted from Sanmugam and Rajanthran [6] and Pati [10]. The questionnaire consisted three sections; first was related to lecturers' demographic profile and the second section focused on the lecturers' perceptions towards research while the third section examined their capability to undertake action research.…”
Section: Methodsmentioning
confidence: 99%
“…However, only 39 lecturers responded to the questionnaire and returned it. The instrument used in this study was a questionnaire which was adapted from Sanmugam and Rajanthran [6] and Pati [10]. The questionnaire consisted three sections; first was related to lecturers' demographic profile and the second section focused on the lecturers' perceptions towards research while the third section examined their capability to undertake action research.…”
Section: Methodsmentioning
confidence: 99%
“…Kho et al (2017) made known that lecturers can distinguish different parts of action research and were able to cite the authors appropriately. Pati (2014) disclosed that teachers had a high perception in researching terms of image, but in terms of time, cost, technicality, and efforts, their attitudes-based perception got low. Basilio et al (2019) also revealed that master teachers have high regard for the value of researching to become better educators.…”
Section: Attitudes Toward Researchmentioning
confidence: 99%
“…Comparing the three models, research capability as a function of motivation to write research, age, and the number of studies completed is more robust. Pati (2014) revealed that Indonesian foreign teachers' perceptions of research were influenced by their capability to conduct action and classroom research. This means that an increase, improvement, or changes in their perception toward research, 7.455 of which can be accounted for their capability to conduct action research.…”
Section: Determinants Of Research Capabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, classroom action research is not as difficult as what is imagined. Classroom action research can be from the daily teaching of teachers in the classroom (Pati, 2014). The teacher only needs to reflect a little on the learning process.…”
Section: The Regression Between Teacher's Interest Toward Teacher's Cmentioning
confidence: 99%